Realization of Optimum Mode of Movement of Roller Forming Installation on Acceleration of Fourth Order - Loveikin, V.; Pochka, К. (Polish Academy of Sciences, 2018)
For the purpose of increase in reliability and durability of roller forming installation the optimum mode of back and forth motion of the forming cart on acceleration of the fourth order is calculated.
Реализация оптимального режима передвижения роликовой формовочной установки на ускорение четвертого порядка
Keywords: roller forming installation; mode of movement; step engine; drive